Contemporary Financial Management. Systematic Literature Review (SLR) - Budi, Budi; Felix, Samuel (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This study presents a systematic literature review (SLR) focusing on the interplay between Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), and their impact on financial performance and firm value. The primary objective is to examine how GCG and CSR practices influence company outcomes, particularly in the context of long-term sustainability and competitive advantage. The research methodology involves the collection and analysis of articles from national and international journals using keywords related to corporate management, financial performance, and CSR. The findings demonstrate a positive correlation between GCG, CSR, and firm value, with financial performance acting as a moderating factor. Companies that adopt robust governance and social responsibility practices tend to exhibit stronger financial outcomes and higher firm value. However, the study also identifies gaps in existing literature, particularly in the consistency of measurement techniques and the need for more research in developing countries. This research provides valuable insights for business practitioners and scholars, emphasizing the importance of integrating ethical practices with corporate management to enhance competitiveness and sustainable growth.